Analysis of the Dimension Chain of Large Crane Reducer - Yan Shidang; Liu Zhongming; Zhang Zhihong; Xiao Weizhong (Jixie chuandong, 2015)
Based on a typical component in the large crane reducer as the object,a three-dimensional tolerance model is established.Through sensitivity numeric analysis,the critical and non-critical dimensions influencing the assembly requirements can be found out,the reasonable distribution of each component tolerances can be achieved,which lays a basis for the optimization of components accuracy design.